Role Strategic Management and Maqasid Sharia Toward Islamic Cooperative Performance - Amar, Faozan; Sumardi, Sumardi; Nugraha, Deni Pandu (Faculty of Economic and Business, 2025)
Research Originality: The study of strategic management and maqasid sharia in Islamic cooperatives is scarce. This study's originality includes maqasid sharia and decision-making styles in the framework of strategic management.Research Objectives: This study aims to determine the roles of strategic management, maqasid sharia, and decision-making style in the performance of Islamic cooperatives and to improve and embed Islamic values in organizations.Research Methods: Questionnaires were distributed to 124 employees of Islamic-cooperative. Furthermore, the study uses structural equation modelling to analyze the questionnaires data from respondents.Empirical Results: The study found that strategic management and organizational performance statistically affect financial performance. Meanwhile, the maqasid sharia and dependent decision-making style have statistically significant indirect effects on financial performance through strategic management and organizational performance.Implications: This study supports the implementation of Maqasid Sharia as the baseline for strategic management. This policy aims to improve the performance of Islamic cooperatives within the limits of Islamic principles. Stakeholders can elaborate on the policy to strengthen strategic management and Maqasid Sharia's implementation.JEL Classification: M21, L21, G40How to Cite:Amar, F., Sumardi, S., & Nugraha, D. P. (2025). Role Strategic Management and Maqasid Sharia Toward Islamic Cooperative Performance. Etikonomi, 24(1), 247 – 264. https://doi.org/10.15408/etk.v24i1.44588.